A new leafhopper genus Geelus and 12 new species (Hemiptera, Cicadellidae, Deltocephalinae) from Southern Africa - Stiller, Michael (Zootaxa, 2020)
Twelve new species in a new genus, Geelus gen.n. are described, 10 species from a confined area in the north- and south-western parts of South Africa and two from Namibia. The genus has been recorded from 35 plant species in 18 families, with one species Geelus dundraad collected on Rooibos Tea, Aspalathus linearis (Fabaceae), which is indigenous to South Africa and cultivated commercially. The 12 new species are Geelus driehoekdraad sp.n., G. drietanddraad sp.n., G. dundraad sp.n., G. haakdraad sp.n., G. kinkeldraad sp.n., G. lemdraad sp.n., G. nektanddraad sp.n., G. platdraad sp.n., G. slangdraad sp.n., G. stompdraad sp.n., G. viertanddraad and G. vurkdraad sp.n. This new genus is allied to the Bonaspeiini, in the Deltocephalinae based on the broad lorum, apically expanded clypellus, dorsal side of the pygofer deeply and broadly incised, large sclerotized segment X, smooth merging of face and crown and Y-shaped connective with short stem. A MaxEnt distribution model based on 19 bioclimatic variables confirmed that the South African species occur within a confined region in the south-western parts of southern Africa.